Implementation of Character Education during the Pandemic In Tk Aisyiyah 1 Gurah Kediri - Futika Permatasari (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2021)
The purpose of this study was to determine the implementation of the Strengthening Character Education policy based on Regulation of the Minister of Education and Culture (Permendikbud) Number 20 of 2018 during the Covid 19 pandemic. This study used a descriptive qualitative research method. The data sources were the principal and teachers in TK Aisyiyah 1 Gurah Kediri. Based on the research results, it is known that there are three stages in the implementation of Strengthening Character Education (PPK), namely through planning, implementation and evaluation activities. Religiosity, nationalism, independence, mutual cooperation, and integrity as character value listed in Permendikbud No. 20 of 2018 are integrated into the kindergarten curriculum, namely aspects of religious and moral values, social emotional, language, cognitive, art, physical motor skills, Al Islam and Kemuhammadiyahan. During the pandemic, learning activities at TK Aisyiyah 1 Gurah were attempted to achieve the target by planning student activities at Home Learning. The learning process uses a portfolio system through groups on one of the messaging platforms. PPK integrated curriculum evaluation is carried out periodically to find out the deficiencies and necessary improvements.